2008
DOI: 10.1007/s00125-008-1206-6
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine autoimmunity in families with type 1 diabetes: frequent appearance of thyroid autoimmunity during late childhood and adolescence

Abstract: Among children of patients with type 1 diabetes, the appearance of thyroid autoantibodies is frequent, is not synchronous to the appearance of other autoantibodies and is most common in late childhood and adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 36 publications
(47 reference statements)
4
28
1
Order By: Relevance
“…Although this study had a modest sample size, other small studies have identified similar results (2,3,9,19,(21)(22)(23)(24), including one in another sample of the Brazilian population (12). According to these authors, thyroid autoantibodies occur in 8% to 25% of FDR of T1DM patients.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Although this study had a modest sample size, other small studies have identified similar results (2,3,9,19,(21)(22)(23)(24), including one in another sample of the Brazilian population (12). According to these authors, thyroid autoantibodies occur in 8% to 25% of FDR of T1DM patients.…”
Section: Discussionsupporting
confidence: 61%
“…P atients with type 1 diabetes mellitus (T1DM) are at increased risk for other autoimmune disorders, such as autoimmune thyroid disease (ATD), celiac disease and Addison's disease (1)(2)(3). The most prevalent autoimmune disease in patients with T1DM is ATD.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations